2011
DOI: 10.1051/0004-6361/201016394
|View full text |Cite
|
Sign up to set email alerts
|

The cosmic web for density perturbations of various scales

Abstract: Aims. We follow the evolution of galaxy systems in numerical simulations. Our goal is to understand the role of density perturbations on various scales in the formation and evolution of the cosmic web. Methods. We perform numerical simulations with the full power spectrum of perturbations, and with a spectrum cut at long wavelengths. In addition, we have one model, where we cut the intermediate waves. We analyse the density field and study void sizes and density field clusters in different models. Results. Our… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 79 publications
0
38
0
Order By: Relevance
“…During the structure formation in the Universe, halo sizes in the supercluster core regions increase, while in void regions halo sizes remain unchanged (Tempel et al 2009). Thus, during the evolution of structure the overall density in superclusters increases, which enhances the evolution of the small-scale protohalos in them (Suhhonenko et al 2011). This may lead to the differences in the properties of galaxy groups and galaxies in them in superclusters and in the field.…”
Section: Discussionmentioning
confidence: 99%
“…During the structure formation in the Universe, halo sizes in the supercluster core regions increase, while in void regions halo sizes remain unchanged (Tempel et al 2009). Thus, during the evolution of structure the overall density in superclusters increases, which enhances the evolution of the small-scale protohalos in them (Suhhonenko et al 2011). This may lead to the differences in the properties of galaxy groups and galaxies in them in superclusters and in the field.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally assumed that the maximal size of these structures is 100−150 Mpc (Frisch et al 1995;Einasto et al 1997;Suhhonenko et al 2011;Aragon-Calvo & Szalay 2013). Quite recently Tully et al (2014) discovered the local supercluster (the "Laniakea") having a diameter of 320 Mpc.…”
Section: Formation Of the Ringmentioning
confidence: 99%
“…Some concern may arise, however, concerning the interpretation of the ring as a true physical structure, and of the causal relationship between the GRBs displaying it. Suhhonenko et al (2011) has pointed out that cosmic structures greater than 140 Mpc in co-moving coordinates did not communicate with one another during the late stage of universal expansion preceding Recombination. The skeleton of the web was created during the inflationary period (Kofman & Shandarin 1988) and evolved slowly following this epoch.…”
Section: Spatial Distribution Of Grbs and Large Scale Structure Of Thmentioning
confidence: 99%
“…In a forthcoming paper we will search for characteristic scales in the distribution of galaxy groups and clusters in more detail. Einasto et al (2011a,b) and Suhhonenko et al (2011) showed how the density waves of different scales affect the richness of galaxy systems. Rich galaxy clusters and high-density cores of superclusters form in regions of high environmental density, where positive sections of medium-and large-scale density perturbations combine.…”
Section: The Shape Of Superclusters As a Test For Cosmological Modelsmentioning
confidence: 99%